DNA vaccines: are they still just a powerful tool for the future? - Beláková, Jana; Horynová, Milada; Krupka, Michal; Weigl, Evzen; Raska, Milan (Archivum immunologiae et therapiae experimentalis, 2007)
Vaccination is historically one of the most successful strategies for the prevention of infectious diseases. For safety reasons, modern vaccinology tends toward the usage of inactivated or attenuated microorganisms and uses predominantly subunit vaccines. The antigens need to be clearly defined, pure, stable, appropriately composed, and properly presented to the immune system of the host. Differing ratios of various proportions between specific CD4+ and CD8+ T cell responses are essential for conferring the required protection in the case of individual vaccines. To stimulate both CD4+ and CD8+ T cells, the antigens must be processed and presented to both antigen-presentation pathways, MHC I and MHC II. Protein antigens delivered by vaccination are processed as extracellular antigens. However, extracellularly delivered antigen can be directed towards intracellular presentation pathways in conjugation with molecules involved in antigen cross-presentation, e.g. heat shock proteins, or by genomic-DNA vaccination. In this overview, current knowledge of the host immune response to DNA vaccines is summarized in the introduction. The subsequent sections discuss techniques for enhancing DNA vaccine efficacy, such as DNA delivery to specific tissues, delivery of DNA to the cell cytoplasm or nucleus, and enhancement of the immune response using molecular adjuvants. Finally, the prospects of DNA vaccination and ongoing clinical trials with various DNA vaccines are discussed.
Keywords: klinické zkoušky jako téma; prezentace antigenu; Lymphocyte Activation; Genetic Vectors; předpověď; Forecasting; aktivace lymfocytů; vakcinace; Drug Delivery Systems; Animals; lidé; Humans; zvířata; tvorba protilátek; Vaccination; genetické vektory; Antibody Formation; Antigen Presentation; DNA vakcíny; Vaccines, DNA; lékové transportní systémy; Clinical Trials as Topic